Development of Teaching Materials for Tahsin Al-Qur'an to Improve Students' Al-Qur'an Reading Ability - Suwarno Suwarno; Andika Hariyanto Surbakti; Ahmad Yunus Mokoginta Harahap; Ramsah Ali (Ta'dib, 2023)
Teaching materials are an important component of learning. Without teaching materials, successful learning will be hampered. In teaching tahsin al-Qur'an at IAIN Takengon there are still no teaching materials available that are appropriate to the learning objectives, thus encouraging the author to develop teaching materials for tahsin al-Qur'an. This research and development aim to produce Al-Qur'an tahsin teaching material products that meet feasibility based on expert assessments. This type of research is Sugiono's Level 1 development model development research. The research was conducted for 6 months at IAIN Takengon. The research subjects consisted of needs analysis subjects, namely first-semester students of the Madrasah Ibtidaiyah Teacher Education study program and lecturers in the Al-Qur'an tahsin course. Data collection techniques use observation, interviews, and questionnaires. Data analysis in this research includes qualitative data analysis and quantitative data analysis. Qualitative data analysis is used to analyze data at the potential and problem stages, as well as literature studies and gathering information. Meanwhile, quantitative data analysis is used at the expert validation stage. The results of the research show that the developed Al-Qur'an tahsin teaching materials meet the feasibility criteria based on expert assessments. the feasibility of teaching materials from material experts got an average score of 4.3 with very valid criteria, from teaching materials experts got an average score of 4.08 with valid criteria, from language, experts got an average score of 4.0 with valid criteria, and design/media experts got an average score of 4.9 with very valid criteria.